2021
DOI: 10.3390/w13111542
|View full text |Cite
|
Sign up to set email alerts
|

Microphytobenthos in the Hypersaline Water Bodies, the Case of Bay Sivash (Crimea): Is Salinity the Main Determinant of Species Composition?

Abstract: In hypersaline water bodies, the microphytobenthos plays a very important ecosystem role and demonstrates variability along with a salinity change. Due to anthropogenic activity, the sharp salinity increase in Bay Sivash occurred after 2014. To assess the changes in the microalgae community during the bay ecosystem transformation, the study was conducted four times in 2018 and 2019. At every sampling period, the samples were taken in a salinity gradient (from 7 to 10 sites). A total of 40 species of microalgae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Hence, in seagrass meadows, oxygen availability generally increases with the distance to the rhizome (Borum et al, 2007). Other macroalgae mats have been shown to inhabit a high abundance of microphytobenthos along a vertical gradient, which is a food source for associated organisms (Shadrin et al, 2019(Shadrin et al, , 2021Prazukin et al, 2020) and causes high phototrophic activity. In the present study, we found a 1.1-fold stronger light gradient over a shorter distance in P. crispa mats, which implies that the layer of high phototrophic activity is in closer proximity to the deeper layer of heterotrophic activity.…”
Section: Potential Relevance For Ecosystem Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in seagrass meadows, oxygen availability generally increases with the distance to the rhizome (Borum et al, 2007). Other macroalgae mats have been shown to inhabit a high abundance of microphytobenthos along a vertical gradient, which is a food source for associated organisms (Shadrin et al, 2019(Shadrin et al, , 2021Prazukin et al, 2020) and causes high phototrophic activity. In the present study, we found a 1.1-fold stronger light gradient over a shorter distance in P. crispa mats, which implies that the layer of high phototrophic activity is in closer proximity to the deeper layer of heterotrophic activity.…”
Section: Potential Relevance For Ecosystem Functionsmentioning
confidence: 99%
“…This associated community benefits from the algal habitat as a food source, substratum for spawning, material for the construction of nests, or shelter from predators (Zaitsev, 2008). Provision of food or protection for rich associated communities are also characteristics of other algal habitats, such as Cladophora mats (Shadrin et al, 2019(Shadrin et al, , 2021Prazukin et al, 2020) or Cystoseira beds (Mineur et al, 2015).…”
Section: Ecological Implicationsmentioning
confidence: 99%
“…The use of new and published data [12,[18][19][20] showed that since the closure of the North Crimean Canal, salinity, TSS, and DOM increased in Bay Sivash (Figure 7). As was shown before, the content of TSS positively correlates with salinity in different water bodies of Crimea [12,22] and different regions [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated cliff erosion may also contribute to the TSS increase in the Bay Sivash. The increase in DOM concentration can probably be explained by the TSS increase and/or the addition to primary production due to the development of floating mats of filamentous green algae Cladophora [4,12,19]. The intensive development of Cladophora in hypersaline water bodies can increase their primary production by more than 10 times [3,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation